2018
DOI: 10.1111/jjns.12240
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making styles, anxiety levels, and critical thinking levels of nurses

Abstract: Aim This research was carried out so as to reveal the relationships between the anxiety state of nurses, their critical thinking disposition, and decision‐making strategies. Methods Survey forms and scales that were related to demographic attributes, anxiety, critical thinking and decision‐making were used in this research. The sampling was formed with 326 nurses who were selected by using the random sampling method. The data were collected between November, 2014 and January, 2015 via a Descriptive Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
2
26
2
Order By: Relevance
“…21 Compared with studies conducted before the Covid-19 outbreak, the state anxiety levels of nurses were higher in this study. 16,22,23 This aspect can be associated with uncertainty, fear of being infected and infecting others, and concerns about shortages of staff and of personal protective equipment due to the outbreak of new infectious diseases such as COVID-19. 9,10,24 In light of these findings, we can say that the state anxiety levels of the nurses providing care for patients with COVID-19 are high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Compared with studies conducted before the Covid-19 outbreak, the state anxiety levels of nurses were higher in this study. 16,22,23 This aspect can be associated with uncertainty, fear of being infected and infecting others, and concerns about shortages of staff and of personal protective equipment due to the outbreak of new infectious diseases such as COVID-19. 9,10,24 In light of these findings, we can say that the state anxiety levels of the nurses providing care for patients with COVID-19 are high.…”
Section: Discussionmentioning
confidence: 99%
“…The sample calculation was made with known average scores of the State and Trait Anxiety Inventory (STAI). The known average score of the state subscale, which is calculated by the number of samples, was based on a reference 16 . The sample size of the study was calculated with the known score (37.1 ± 8.9) using the formula n = (t2 × s2)/d2 and determined to be 1217 nurses 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to privacy, we observed that anxiety does not influence the nurses' concept of privacy. This could be explained because privacy is a complex concept, defined by four elements: (i) solitude, (ii) reserve, (iii) intimacy, and (iv) anonymity [52], and some of them are impossible to apply correctly in the nursing work environment, where they are more focused on privacy from a physical dimension but not from a psychosocial dimension [53]. About self-reliance, it is a competence associated with the self-confidence in your own ability to make decisions [54].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing requires intensive concentration and independent thinking to make health‐related decisions for patients. Anxiety can interfere with the ability of nurses to make appropriate decisions (Polat et al, 2019) and can thus result in mistakes and a reduction of nursing quality.…”
Section: Introductionmentioning
confidence: 99%